A call for comparative effectiveness research to learn whether routine clinical care decisions can protect from dementia and cognitive decline. Issue 1 (December 2016) - Dacks, Penny; Armstrong, Joshua; Brannan, Stephen; Carman, Aaron; Green, Allan; Kirkman, M.; Krakoff, Lawrence; Kuller, Lewis; Launer, Lenore; Lovestone, Simon; Merikle, Elizabeth; Neumann, Peter; et al.
Abstract Common diseases like diabetes, hypertension, and atrial fibrillation are probable risk factors for dementia, suggesting that their treatments may influence the risk and rate of cognitive and functional decline. Moreover, specific therapies and medications may affect long-term brain health through mechanisms that are independent of their primary indication. While surgery, benzodiazepines, and anti-cholinergic drugs may accelerate decline or even raise the risk of dementia, other medications act directly on the brain to potentially slow the pathology that underlies Alzheimer's and other dementia. In other words, the functional and cognitive decline in vulnerable patients may be influenced by the choice of treatments for other medical conditions. Despite the importance of these questions, very little research is available. The Alzheimer's Drug Discovery Foundation convened an advisory panel to discuss the existing evidence and to recommend strategies to accelerate the development of comparative effectiveness research on how choices in the clinical care of common chronic diseases may protect from cognitive decline and dementia.